PERKAWINAN LINTAS BUDAYA SEBAGAI BENTUK FENOMENA KESENJANGAN SOSIAL DALAM NOVEL SALAH ASUHAN: KAJIAN POSTKOLONIALISME - Ika Shinthya Yusriana; Muh. Fatoni Rohman (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2023)
Cross-Cultural Marriage as a Form of Social Inequality Phenomenon in the Novel Wrong Upbringing: A Study of Postcolonialism. This study aims to identify and describe the concept and problems of mixed marriage as a result of the hegemony of the West as a dominating nation during the colonial period and its background as reflected in the novel Wrong Upbringing by Abdoel Moeis, using a postcolonialism theory approach. The method used is descriptive-qualitative, using note-taking and literature study in collecting the data and the interactive Miles and Huberman technique in analyzing the data. The results obtained were in the form of two mixed marriage concepts with negative images, namely experiencing failure and rejection caused by the hegemony of the West during the colonial period. This is the background for the excessive westernization of Hanafi's character.